2007
DOI: 10.1002/ajpa.20734
|View full text |Cite
|
Sign up to set email alerts
|

The evolution of human reproduction: A primatological perspective

Abstract: Successful reconstruction of any aspect of human evolution ideally requires broad-based comparisons with other primates, as recognition of general principles provides a more reliable foundation for inference. Indeed, in many cases it is necessary to conduct comparisons with other placental mammals to test interpretations. This review considers comparative evidence with respect to the following topics relating to human reproduction: (1) size of the testes, sperm, and baculum; (2) ovarian processes and mating cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
152
2
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 207 publications
(163 citation statements)
references
References 227 publications
(154 reference statements)
8
152
2
1
Order By: Relevance
“…Although the great apes also share haemochorial placentation, trophoblast invasion is deepest in the human [87]. This is consistent with the theory that greater access to the maternal blood supply facilitates growth of our large fetal brain [88]. However, the deep invasion comes at a price, for it is associated with an increased risk of complications of pregnancy, such as pre-eclampsia [89].…”
Section: Resultssupporting
confidence: 76%
“…Although the great apes also share haemochorial placentation, trophoblast invasion is deepest in the human [87]. This is consistent with the theory that greater access to the maternal blood supply facilitates growth of our large fetal brain [88]. However, the deep invasion comes at a price, for it is associated with an increased risk of complications of pregnancy, such as pre-eclampsia [89].…”
Section: Resultssupporting
confidence: 76%
“…The developmental basis of the evolution of large brain size in humans has often been considered to be an exceptional prolongation of postnatal brain growth, creating enhanced opportunities for environmental input to the developing brain (31)(32)(33). However, Vinicius (34) showed that the ways in which human brain and body growth patterns depart from those of other primates are more complex than this, including at least three distinct mechanisms: (i) a moderate extension of postnatal brain growth, (ii) a derived developmental allometry, and (iii) a retardation of postnatal body growth.…”
Section: Discussionmentioning
confidence: 99%
“…Although seasonal fluctuations in testes size are well documented in species with breeding seasons, surprisingly little is known about the relative stability of testes size in humans (23) or about the environmental, social, or nutritional factors that may influence it, and thus, it remains unclear whether greater testes volume is a cause or a consequence of male life-history strategies. If testicular volume is causal, individual differences in testes may be governed by evolved genetic influences, or they may be shaped by environmental factors analogous to the role of father absence in the timing of female menarche (36).…”
Section: Discussionmentioning
confidence: 99%
“…23). For example, among primates, monogamy and single-male polygyny are associated with smaller testes size compared with multimale, multifemale breeding systems.…”
mentioning
confidence: 99%